MHealth as a primary mode of intervention for women at risk of, or diagnosed with, gestational diabetes: a scoping review protocol. Issue 3 (16th March 2021) - Edwards, Katie J.; Maslin, Kate; Andrade, Jackie; Jones, Ray B.; Shawe, Jill
ABSTRACT: Objective: To synthesize current knowledge on the use of mHealth as a primary mode of intervention for the prevention and management of gestational diabetes mellitus and its long-term implications among women at risk of, or diagnosed with, gestational diabetes mellitus. Introduction: Prevention and management of gestational diabetes mellitus and its associated adverse outcomes are of paramount importance to both maternal and infant health. However, women with experience of gestational diabetes mellitus report several barriers to effective disease management and lifestyle change. Supporting women through use of mHealth technology may help overcome these barriers. Recent evidence suggests mobile apps may be useful for the prevention and management of gestational diabetes mellitus, however, less is known about the broader application of mHealth from preconception to interconception. Inclusion criteria: Studies considered for inclusion are those focused on the use of mHealth as the primary mode of intervention for the prevention and management of gestational diabetes mellitus and its long-term implications among women at risk of, or diagnosed with, gestational diabetes mellitus. Studies will be limited to those published in English, with no date restrictions. Methods: The following databases will be searched: MEDLINE (Ovid), CINAHL (EBSCO), EMBASE (Ovid), Cochrane Database (Wiley), Scopus, and TRIP. Unpublished studies and gray literature will be searched using Open Grey, ISRCTN Registry, ClinicalTrials.gov, EU Clinical Trials register, and ANZCTR. Two reviewers will independently screen abstracts. Reviewers will assess full texts of selected citations against the inclusion criteria. Any disagreements will be discussed with a third reviewer. Data will be extracted and presented in diagrammatic or tabular form with an accompanying narrative in line with review objectives.